The Symbolic Meaning of the Lemon Basidakah Tradition in Nagari Kinari, Bukit Sundi District, Solok Regency, West Sumatra Province - Rahmawati, Mila; Yulika, Febri (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research is entitled "The Tradition of Basidakah Limau in Nagari Kinari, Bukit Sundi District, Solok Regency, West Sumatra Province". The purpose of this study is to describe the procession of the lime basin tradition in Nagari Kinari and to describe the symbolic meaning of the lime basin tradition. The theory used in this study is the symbolic interpretive theory of Clifford Geertz. The methods used in this study were carried out by observation, interview and documentation methods. The data analysis technique in this study uses steps including data reduction, data presentation, and conclusion drawing and verification. The results of this study show that the procession of the lime basidakah tradition starts from determining the date and day, making pucuak, making musajik-musajik cakes, making lime water, picking up pucuak by pasumandan to the place where pucuak is made, the lime sidakah event takes place, and the delivery of pucuak to the cemetery by Pasumandan. Furthermore, the symbolic meaning of the lime basidakah tradition is pucuak which means as an intermediary or the meaning of apology for people who have died, banana stems mean the Nagari Kinari community which is the foundation and support of tradition, carano means traditional meaning and also the meaning of respect for ancestors, flowers mean life and beauty, musajik-musajik cakes means hope for life that is lived full of sweetness and always an abundance of affection, lime water means to cleanse the heart and mind from bad intentions, grudges, or past mistakes and also symbolizes hope and renewal of life, baju bundo kanduang means depicting the role, dignity, and responsibility of women in Minangkabau, and coins mean alms and generosity.